Paraquat Training, Licensing, and Equipment Requirements - Brett W. Bultemeier (EDIS)
Paraquat is unique among pesticides in that it requires all who use it to be licensed. After a pesticide license is attained additional training is required on a 3 year basis. Furthermore, there are specific packaging and equipment requirements to legally use this product. This document serves to outline these requirements and explain how to fulfill them for pesticide applicators in Florida and around the country.